Structure and dynamics of the drug-bound bacterial transporter EmrE in lipid bilayers - Alexander A. Shcherbakov (Nature Portfolio, 2021)
The small proton-coupled transporter EmrE confers multidrug resistance in bacteria. The structure of drug-bound EmrE in phospholipid bilayers is now determined using solid-state NMR. The structure provides detailed insights into the molecular mechanism of substrate recognition by this transporter.